Measuring the cost of COVID-19 in terms of the rise in the unemployment rate: The case of Spain - Juan Carlos Cuestas; Javier Ordó\~nez; Mercedes Monfort (Economics: The Open-Access, Open-Assessment Journal, 2021)
In this article, we aim to estimate what the cost of Covid-19 has been in terms of unemployment for Spain. We use a simple autoregressive model to simulate what the unemployment rate would have been without the pandemic and we compare this with the actual values. We also forecast the unemployment rate for 2021 and 2022 to analyse the persistence of the pandemic shock to unemployment.
Keywords: C22; F15; 330; Covid-19; persistence; Spain; unemployment